# -5(w+2)-w-3=-6(w+5)+16

## Simple and best practice solution for -5(w+2)-w-3=-6(w+5)+16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for -5(w+2)-w-3=-6(w+5)+16 equation:

Simplifying
-5(w + 2) + -1w + -3 = -6(w + 5) + 16

Reorder the terms:
-5(2 + w) + -1w + -3 = -6(w + 5) + 16
(2 * -5 + w * -5) + -1w + -3 = -6(w + 5) + 16
(-10 + -5w) + -1w + -3 = -6(w + 5) + 16

Reorder the terms:
-10 + -3 + -5w + -1w = -6(w + 5) + 16

Combine like terms: -10 + -3 = -13
-13 + -5w + -1w = -6(w + 5) + 16

Combine like terms: -5w + -1w = -6w
-13 + -6w = -6(w + 5) + 16

Reorder the terms:
-13 + -6w = -6(5 + w) + 16
-13 + -6w = (5 * -6 + w * -6) + 16
-13 + -6w = (-30 + -6w) + 16

Reorder the terms:
-13 + -6w = -30 + 16 + -6w

Combine like terms: -30 + 16 = -14
-13 + -6w = -14 + -6w

Add '6w' to each side of the equation.
-13 + -6w + 6w = -14 + -6w + 6w

Combine like terms: -6w + 6w = 0
-13 + 0 = -14 + -6w + 6w
-13 = -14 + -6w + 6w

Combine like terms: -6w + 6w = 0
-13 = -14 + 0
-13 = -14

Solving
-13 = -14

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.`